DIFFERENCE AMONG RANKING ALGORITHMS OF DIFFERENT WEB SEARCH TOOLS: A STATISTICAL APPROACH - Moghaddam, Alireza Isfandyari; Ranjbar, Vahid (Malaysian Journal of Library and Information Science, 2017)
One of evaluation studies examining web search tools is ranking algorithm area. Accepting the idea that different search tools do use different ranking algorithms, the present research aims to confirm such an idea using a statistical approach. To do this, five metasearch engines (MSEs) namely Ez2find, Dogpile, MetaCrawler, Info and WebCrawler along with their four common underlying single search engines (SEs) – Google, Yahoo!, Msn (currently called Windows Live Search) and Ask – have been applied. To conduct the research five queries have been utilized. For comparing ranking algorithms of these web search tools, statistical tests "Kruskal-Wallis" and "Tukey HSD" were utilized. The findings indicate and confirm that different search tools on the web make use of different ranking algorithms. In other words, this research supports findings of previous studies.